Two Studies of Autonomous Sensory Meridian Response (ASMR): The Relationship between ASMR and Music-Induced Frisson - Kovacevich, Alexsandra; Huron, David (Empirical Musicology Review, 2019)
In recent years, a widely popular phenomenon has emerged as exemplified in thousands of videos available on the Internet. Referred to using the impressive sounding term "Autonomous Sensory Meridian Response" (abbreviated ASMR), followers claim that ASMR videos evoke a special "tingling" sensation that is regarded as highly pleasurable and relaxing. The popularity of this phenomenon is reflected in individual ASMR videos receiving more than 43 million views and a reddit ASMR forum with over 130,000 subscribers. Two exploratory studies are reported. In the first study, a content analysis was carried out on 30 popular ASMR videos, and compared with 30 videos employing two different control methods. In the second study, a content analysis was carried out on 3,600 comments on discussion forums and accompanying ASMR videos. The results indicate that ASMR videos typically employ a quiet, private scene, with a relaxed, friendly, and intimate actor ("ASMRtist"). Although ASMR is evoked by non-musical stimuli, the physiological responses to ASMR (skin-related tingling and goosebumps) strongly resemble the classic frisson experience—a phenomenon that has received considerable attention among music perception researchers. Careful consideration of ASMR stimuli and responses suggest that ASMR is consistent with Huron's (2006) theory of frisson.